Comparison of the Efficacies of Parenteral Iron Sucrose and Oral Iron Sulfate for Anemic Patients with Inflammatory Bowel Disease in Korea - Han, Yoo Min (Gut Liver, 2016)
BACKGROUND/AIMS: The optimal route for iron administration in anemic patients with inflammatory bowel disease (IBD) has not been determined. The aim of this study was to compare the efficacies of parenteral and oral iron therapy in IBD patients in Korea. METHODS: A retrospective multicenter study was performed. Patients who had been administered parenteral iron were matched to the controls with oral iron at a 1:1 ratio according to age, sex, and type of IBD. RESULTS: Patients that received parenteral iron exhibited increases in hemoglobin levels of ≥20% from the baseline at lower doses and in shorter durations (p=0.034 and p=0.046, respectively). In the multivariate analysis, parenteral iron therapy appeared to be more efficient than oral iron therapy, but this difference was not statistically significant (hazard ratio [HR], 1.552; 95% confidence interval [CI], 0.844 to 2.851; p=0.157). Patients with ulcerative colitis responded better to iron therapy than those with Crohn’s disease (HR, 3.415; 95% CI, 1.808 to 6.450; p<0.001). Patients with an initial hemoglobin level of 10 g/dL or higher responded poorly to iron therapy (HR, 0.345; 95% CI, 0.177 to 0.671; p=0.002). CONCLUSIONS: Parenteral iron therapy appears to be more efficient than oral iron therapy. Physicians should focus on the iron deficiency of IBD patients and consider parenteral iron supplements in appropriate patient groups.